2021
DOI: 10.1001/jamanetworkopen.2021.36560
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variant at Chromosome 12q23.1 With Neuropathic Pain Susceptibility

Abstract: Key Points Question Are genetic variants associated with neuropathic pain (NP) susceptibility? Findings This genetic association study included a meta-analysis of 3 genome-wide association studies, with 4512 individuals with NP and 428 489 without, all with European descent, and identified a novel genome-wide significant locus at chromosome 12q23.1 near SLC25A3 and a suggestive locus at chromosome 13q14.2 near CAB39L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 63 publications
(128 reference statements)
0
21
0
Order By: Relevance
“…Although genetic factors have not been analysed in this study, they have been studied separately elsewhere in DOLORisk Dundee [ 77 ]. These two components should be brought together to analyse the relative contribution of genetic and environmental factors to neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although genetic factors have not been analysed in this study, they have been studied separately elsewhere in DOLORisk Dundee [ 77 ]. These two components should be brought together to analyse the relative contribution of genetic and environmental factors to neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this should be a focus of future work. Similarly, future studies will explore the wealth of genetic data that is available within UK Biobank, both to validate recent findings and to potential identify novel associations [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models have suggested that SLC25A3 is believed to have a role in developing neuropathic pain; however, further research is required to better understand the underlying mechanisms implicated with these findings. 91 This study illustrates the use of common-effect models to provide important insights into the potential genetic associations to neuropathic pain.…”
Section: Meta-analysis Modelsmentioning
confidence: 95%
“…Veluchamy et al performed meta-analyses investigating the association of genetic variants on the susceptibility to neuropathic pain. 91 The authors performed meta-analyses of genome-wide association studies from 3 large comparable cohorts of patients with neuropathic pain in the United Kingdom. Using common-effect meta-analyses of each single-nucleotide polymorphism, 60 they identified a novel genome-wide significant locus at chromosome 12q23.1 mapping to SLC25A3 (odds ratio = 1.68, 95% confidence interval [CI]: 1.40–2.02).…”
Section: Meta-analysis Modelsmentioning
confidence: 99%